Sladkoe slovo "Svoboda" . Sladkoe slovo "Svoboda" . Sweet Word "Freedom" . Сладкое слово "Свобода" - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. International experts' seminar on "Russia's epochal crisis". Featured in the program: Pavlenko, Sergei (Economist) Международный экспертный семинар "Россия на переломе эпох". В программе участвуют: Павленко, Сергей (Экономист)